2013
DOI: 10.1109/jlt.2013.2265774
|View full text |Cite
|
Sign up to set email alerts
|

Compact Multimode Polymer Waveguide Bends for Board-Level Optical Interconnects

Abstract: Multimode polymer waveguides are promising for use in board-level optical interconnects. In recent years, various on-board optical interconnection architectures have been demonstrated making use of passive routing waveguide components. In particular, 90 bends have played important roles in complex waveguide layouts enabling interconnection between non co-linear points on a board. Due to the dimensions and index step of the waveguides typically used in on-board optical interconnects, low-loss bends are typicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…0.25dB per 90 • bend) when the bending radius becomes smaller than 4 mm. This corresponds with the results in [25], in which the bending losses of 50 µm x 50 µm waveguides (with an NA of 0.25 and 1.14) were simulated using ray tracing simulations. It was found that the bending loss of a single 90 • bend becomes higher than 0.25dB for bending radii between 3 and 9 mm, depending on the incoupling conditions and the numerical aperture of the simulated waveguide.…”
Section: Influence Of Waveguide Bendingsupporting
confidence: 83%
See 1 more Smart Citation
“…0.25dB per 90 • bend) when the bending radius becomes smaller than 4 mm. This corresponds with the results in [25], in which the bending losses of 50 µm x 50 µm waveguides (with an NA of 0.25 and 1.14) were simulated using ray tracing simulations. It was found that the bending loss of a single 90 • bend becomes higher than 0.25dB for bending radii between 3 and 9 mm, depending on the incoupling conditions and the numerical aperture of the simulated waveguide.…”
Section: Influence Of Waveguide Bendingsupporting
confidence: 83%
“…These are typical dimensions for multimode waveguides providing 1dB alignment tolerances larger than ±10 µm for in-and outcoupling [25]. To maximize the light confinement, the refractive index contrast between cladding and core was chosen as large as possible within the limits of available materials.…”
Section: Waveguide Design and Materialsmentioning
confidence: 99%
“…The total bend losses α were measured by a setup shown in Fig. 5 and then they were calculated from (10). The bend losses A modified with regard to the lengths of the bend waveguides were then calculated from (11):…”
Section: Resultsmentioning
confidence: 99%
“…Such basic building blocks have been developed for a couple of years and are also well characterized which concerns their utilization in the single-mode regime [3][4][5]. In the literature several types of optical bend waveguides have been already presented:  bend waveguides described by D. Israel [6] and S. Musa [7]; this will be in more details mentioned later,  single-mode polymer SU-8 2000 waveguide [8], with thickness around 1.7 µm and having different core widths (1.2, 1.6, 2.0, 2.4 and 2.8 µm) and bending radius (300, 200, 150, 100, 75, 50 and 25 µm),  multimode bend optical waveguides based on silicon rib structures (height of 28 μm and width 25 μm); these S-bend structures have the radius ranging from 2 to 20 mm and the bend offset 0.5 mm [9],  fully embedded and air-exposed curved waveguides with a 50 µm × 50 μm cross section having 10 mm bending radius limit [10],  90° bend and S-bend siloxane OE-4140 (core) and OE-414 (cladding) multimode waveguides having typical dimensions 50 µm × 50 µm [11],  multimode bend waveguides with dimensions 50 µm × 50 µm, 75 µm × 50 µm and 100 µm × 50 µm (wide × high) made of acrylate polymer Truemode TM from Exxelis Limited deposited on FR4 wafer intended for wavelength of 850 nm and the refractive index of the core was n core = 1.5560 and that of the cladding was n clad = 1.5264 [12],  polymer multimode waveguide splitter having input waveguide core width 100 µm and ended by S-bend waveguide with different core widths (20, 40, 60 and 80 µm); detailed study was presented in [13].…”
Section: Introductionmentioning
confidence: 99%
“…While polymer-waveguides based interconnect technologies and fixed fiber based interconnects have been proven to be effective alternatives to copper-based card-to-card interconnects [2,3], providing high-speed reconfigurable optical interconnects that meet the emerging requirements of flexible connectivity has become a major challenge. In previous studies, reconfigurable optical interconnects architecture based on free-space optical technology has been demonstrated [4][5][6].…”
Section: Introductionmentioning
confidence: 99%